Peranan Wanita Tani dalam Kegiatan Produksi Gula Aren Terhadap Kontribusi Pendapatan Rumah Tangga di Kelurahan Kassa Kecamatan Batulappa Kabupaten Pinrang - nurhaedah nurhaedah; Yusriani Yusriani; Irmayani Irmayani (Universitas Muslim Maros, 2023)
The study aims 1) to determine the role of farm women the sugar palm production activities in Kassa Village, Batulappa District, Pinrang Regency. 2) to determine the income derived from the sugar palm production activities in Kassa Village, Batulappa District, Pinrang Regency. 3) to determine the income contribution of sugar palm production to total household income in Kassa Village, Batulappa District, Pinrang Regency. The type of data used in this research is descriptive quantitative. The research starts from February to March 2019 in the Kassa Village, Batulappa District, Pinrang Regency. Data collection techniques used were observation and interview, the source of the data used is the primary and secondary data. The data analysis used on this research is quantitative description. The results showed that 1) the results of this study indicate that the level of the role of female farmers in the production of sugar palm in the Kassa Village, Batulappa District, Pinrang Regency in midle category with the persentage of 74%. 2) the average income that farmers earn in the Kassa Village, Batulappa District, Pinrang Regency production activities is Rp 1.712.505, per month. 3) The contributions of sugar palm income to household income is 45,96%.